2010
DOI: 10.1152/ajpregu.00208.2009
|View full text |Cite
|
Sign up to set email alerts
|

The antidiuretic neurohormone RhoprCAPA-2 downregulates fluid transport across the anterior midgut in the blood-feeding insect Rhodnius prolixus

Abstract: Osmotic balance in insects is regulated by the excretory system, consisting of Malpighian tubules and the gut under the control of diuretic and antidiuretic factors. Terrestrial insects must conserve water, and antidiuresis is the norm, only interrupted by brief diuretic periods. Surprisingly, little is known about antidiuresis in insects. Two antidiuretic strategies have been described. The first antidiuretic mechanism involves the reabsorption of fluid from the primary urine in the hindgut. More recently, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
19
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 57 publications
5
19
0
2
Order By: Relevance
“…In this study, we show expression data for a CAPA receptor homolog in R. prolixus that correlates with the physiological roles identified previously in the MTs (9) and anterior midgut (4,11). Interestingly, we have identified that additional tissues that comprise the alimentary canal contain appreciable levels of CAPA receptor expression, namely in oesophagus posterior midgut, and hindgut, suggesting additional targets for the endogenous CAPA peptides.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In this study, we show expression data for a CAPA receptor homolog in R. prolixus that correlates with the physiological roles identified previously in the MTs (9) and anterior midgut (4,11). Interestingly, we have identified that additional tissues that comprise the alimentary canal contain appreciable levels of CAPA receptor expression, namely in oesophagus posterior midgut, and hindgut, suggesting additional targets for the endogenous CAPA peptides.…”
Section: Discussionsupporting
confidence: 86%
“…The capa-r1 expressed receptor was activated by low concentrations of RhoprCAPA-α2 with an EC 50 value comparable to that determined for other heterologously expressed CAPA receptors (13,14); however, this EC 50 value does not match the observed in vitro potency observed for RhoprCAPA-α2, which lies in the low nanomolar range (4,9), and this difference may be a result of poor coupling of the receptor to the calcium mobilization pathway leading to nonoptimal activation of the aequorin reporter. In support of this prediction, our recent physiological results suggest that calcium is not involved in eliciting the natural RhoprCAPA-α2 inhibitory effect on the anterior midgut (4); thus, the endogenous receptor coupling in vivo differs from that in our heterologous expression system.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations